Crossing the interaction divide between international and domestic students in higher education. - Arkoudis, Sophie; Baik, Chi (HERDSA Review of Higher Education v.1 p.47-62, 2014)
One of the challenges facing higher education institutions (HEIs) across the world is to find fruitful and productive ways to increase interaction between domestic and international students. This article presents an overview of recent research in this area in order to identify ways that HEIs can make a significant leap forward in addressing this issue. The article outlines the research into this issue and highlights the Interaction for Learning Framework as a significant study that is informed by research and practice that can guide academics in enhancing peer interaction between domestic and international students. The article concludes by outlining some key considerations for integrating the framework within broader institutional strategies that focus on internationalising the student experience at home for all students. [Author abstract]